The Effects Of Exchange Rate And Interest Sensitivity, Managerial Ownership, And Institutional Ownership On Financial Distress - Refni, Zumaira; Haryetti, Haryetti; Fathoni, Ahmad Fauzan (International Journal of Economic, Business & Applications, 2021)
Financial distress is a situation where a company is unable to repay debts that are past due, both short-term debt and long-term debt. So that it can cause the company's operational activities to be disrupted and bankrupt. This study examines the effect of exchange rate sensitivity, interest rate sensitivity, managerial ownership, and institutional ownership on financial distress. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. From this population, this research used 62 manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period as samples. This research uses a logistic regression analysis method. The results showed that the variable of exchange rate sensitivity has a significant negative effect on financial distress. Interest rate sensitivity has a significant positive impact on financial distress, managerial ownership has no significant positive effect on financial distress, and institutional ownership has no significant positive effect on financial distress. This shows that companies need to pay attention to exchange rate sensitivity and interest rate sensitivity because of the higher the sensitivity level, the worse it will have on the company.